Molecular Mechanisms and Drug Development in Aquaporin Water Channel Diseases: Structure and Function of Aquaporins - Masato Yasui (Elsevier, 2004)
The discovery of the water channel aquaporin has greatly expanded our understanding of the regulation of the water permeability of biological membranes. The atomic structure of aquaporin-1 (AQP1) demonstrated how aquaporin is freely permeated by water but not protons and provided marked insight into several human disorders. Eleven mammalian aquaporins have been identified, each with a distinct distribution, and these are selectively permeated by water or water plus glycerol. Aquaporins are suspected in numerous pathological conditions involving fluid transport such as brain edema. Knowledge of aquaporin structure may provide insight into the development of new therapeutics through appropriate drug design. Keywords:: aquaporin-1, permeability, water channel, structure and function, human disease